2022
DOI: 10.1038/s41598-022-13799-6
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic CA1 neurons are more stable following context changes than glutamatergic cells

Abstract: The CA1 region of the hippocampus contains both glutamatergic pyramidal cells and GABAergic interneurons. Numerous reports have characterized glutamatergic CAMK2A cell activity, showing how these cells respond to environmental changes such as local cue rotation and context re-sizing. Additionally, the long-term stability of spatial encoding and turnover of these cells across days is also well-characterized. In contrast, these classic hippocampal experiments have never been conducted with CA1 GABAergic cells. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
(91 reference statements)
1
1
0
Order By: Relevance
“…Here, we demonstrated that spatial FS neurons in LEC and CA1 remapped in different spatial contexts. This further substantiates the notion that FS neurons contribute to feature coding in the networks that they are embedded in 18,43,44,47,62 .…”
Section: Discussionsupporting
confidence: 81%
“…Here, we demonstrated that spatial FS neurons in LEC and CA1 remapped in different spatial contexts. This further substantiates the notion that FS neurons contribute to feature coding in the networks that they are embedded in 18,43,44,47,62 .…”
Section: Discussionsupporting
confidence: 81%
“…To drive GCaMP expression, we used human synapsin I gene promoter, which promotes transgene expression in both excitatory and inhibitory cells. Recent studies have reported that a subset of inhibitory cells in the CA1 show spatial and environmental modulation in activity (Geiller et al, 2020; Schuette et al, 2022). Therefore, it will be of interest and value to study the relationship between gA/gPC indices and subtypes of neurons.…”
Section: Discussionmentioning
confidence: 99%